2012
DOI: 10.1371/journal.pone.0041788
|View full text |Cite
|
Sign up to set email alerts
|

A Quorum Sensing-Disrupting Brominated Thiophenone with a Promising Therapeutic Potential to Treat Luminescent Vibriosis

Abstract: Vibrio harveyi is amongst the most important bacterial pathogens in aquaculture. Novel methods to control this pathogen are needed since many strains have acquired resistance to antibiotics. We previously showed that quorum sensing-disrupting furanones are able to protect brine shrimp larvae against vibriosis. However, a major problem of these compounds is that they are toxic toward higher organisms and therefore, they are not safe to be used in aquaculture. The synthesis of brominated thiophenones,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 38 publications
2
48
0
2
Order By: Relevance
“…A similar decrease in bioluminescence was observed in double mutants that are only sensitive to one of the three signal molecules and mutants with a constitutively active quorum-sensing-signal transduction cascade (data not shown). In order to further investigate the possibility that the effect observed in the bioluminescence experiments was due to minor toxicity, we investigated the effect of the compounds on the bioluminescence of strain JAF548 pAKlux1, in which bioluminescence is independent of the quorum-sensing system (12). We found that the luminescence in this strain was also inhibited by pyrogallol, similar to what was observed with wild-type Vibrio harveyi (Fig.…”
supporting
confidence: 54%
“…A similar decrease in bioluminescence was observed in double mutants that are only sensitive to one of the three signal molecules and mutants with a constitutively active quorum-sensing-signal transduction cascade (data not shown). In order to further investigate the possibility that the effect observed in the bioluminescence experiments was due to minor toxicity, we investigated the effect of the compounds on the bioluminescence of strain JAF548 pAKlux1, in which bioluminescence is independent of the quorum-sensing system (12). We found that the luminescence in this strain was also inhibited by pyrogallol, similar to what was observed with wild-type Vibrio harveyi (Fig.…”
supporting
confidence: 54%
“…Defoirdt and co-workers made the sulphur analogs of brominated furanones (brominated thiophenones, such as 124 and 125 (Figure 16), and showed that at low micromolar concentrations these compounds could block quorum sensing in V. harveyi , via the QS master regulator LuxR [126]. …”
Section: Small Molecule Inhibitors Of Ai-2 Signalingmentioning
confidence: 99%
“…harveyi wild type strain BB120 and mutants BB170 (luxN::Tn5kan), BB886 (luxPQ::Tn5kan) and BB721 (luxO::Tn5lacZ) were acquired from ATCC. To evaluate the QS inhibitory activity of the flavonoids, a screening procedure was adapted from (Defoirdt et al, 2007(Defoirdt et al, , 2012, with slight modifications. Bacteria were cultured in Luria-Bertani medium containing 35 g/l sea salts (Sigma-Aldrich).…”
Section: Quorum Sensing Assaysmentioning
confidence: 99%